2020
DOI: 10.1177/2055668320968476
|View full text |Cite
|
Sign up to set email alerts
|

OASIS 1: Retrospective analysis of four different microprocessor knee types

Abstract: Introduction Microprocessor knee analyses to date have been primarily limited to microprocessor knees as a category rather than comparisons across different models. The purpose of the current analysis was to compare outcomes from four common knee models. Methods A retrospective analysis of clinical outcomes was performed. Outcomes for functional mobility, quality of life, satisfaction with amputee status, and injurious falls were compared. Specific knee types represented were C-Leg (Ottobock), Orion (Blatchfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In principle, BAP fitted with MPKs and ESARs could increase stability (e.g., stance and swing control), walking capacity (e.g., high range of motion, mechanically-powered push off), attenuation of excessive loading during daily activities (e.g., auto adaptive stance and swing phases) and reduce risks of falls (e.g., automatic stumble recovery) (Campbell et al, 2020;Frossard, 2013;Highsmith et al, 2010;Kahle et al, 2008;Orendurff et al, 2006;Sawers and Hafner, 2013). One could hypothesise that these functions altogether might generate a loading profile within the Goldilocks Zone for the osseointegrated implant.…”
Section: Importance Of Loading Profilementioning
confidence: 99%
“…In principle, BAP fitted with MPKs and ESARs could increase stability (e.g., stance and swing control), walking capacity (e.g., high range of motion, mechanically-powered push off), attenuation of excessive loading during daily activities (e.g., auto adaptive stance and swing phases) and reduce risks of falls (e.g., automatic stumble recovery) (Campbell et al, 2020;Frossard, 2013;Highsmith et al, 2010;Kahle et al, 2008;Orendurff et al, 2006;Sawers and Hafner, 2013). One could hypothesise that these functions altogether might generate a loading profile within the Goldilocks Zone for the osseointegrated implant.…”
Section: Importance Of Loading Profilementioning
confidence: 99%
“…The PLUS-M instrument is described in detail in prior work, but briefly, the instrument was administered in the 12-item short form (v1.2). 17 , 18 The instrument assesses mobility on 12 different tasks. The result is a raw score that is converted to a calibrated T-Score on a continuous scale ranging from 0–100, with 50.0 representing the population average score.…”
Section: Methodsmentioning
confidence: 99%
“…12 Since, studies showed that the use and satisfaction of prosthetic lower limb could be significantly improved when using advanced components such microprocessor-controlled knees compared to a nonmicroprocessor-controlled knees. 9,13, 14 Satisfactory prosthetic fitting might be compromised because of incongruous shapes of residuum (e.g., length, bulbous, volume change) and/or skin issues. [15][16][17] Paterno et al (2018) and Meulenbelt et al (2009) report that that 63-82% of lower limb amputees have problems with skin lesions.…”
Section: Role Of Prosthetic Carementioning
confidence: 99%